Tipi di concessive in italiano antico - Consales, Ilde (Verbum – Analecta Neolatina, 2002)
The connection of concession assumes particular configurations in the 13th and 14th-centuries language. The period shows a rich variety of concessive clauses. We can distinguish about eleven different types of concessives. These configurations are distribuited on a continuum which has sub-clauses and main clauses as its extreme ends.